Fraktale Doppel-Boom-Zyklen und Querschnittstechnologien: Theorie, Empirie und Politikimplikationen am Beispiel der Nanotechnologie - Kreuchauff, Florian Heiko (KIT Scientific Publishing, 2016)
In a majority of knowledge-intensive technologies, empirical studies show characteristic double boom patterns of research activities. After an initial increase of efforts, research activities drop, only to rise again after a certain period. As a reason for this interim weakening the literature presumes a temporary disillusionment among economic actors. The present work questions this assumption. Instead, it is argued that a general purpose technology is replacing its techno-economic predecessor.